Pengaruh Dana Perimbangan Yang Dimoderasi Belanja Langsung Terhadap Kesejahteraan Masyarakat - Permata, Anak Agung Imas; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Human development is essentially the process of expanding human choices. Human Development Index is an indicator of the level of The Public Welfare. In terms of balancing funds and direct Purchasing, the purpose of administration is to increase service standards and make the public welfare become better, which can be seen from the human development index as an indicator of public welfare. Economic growth is important to maintain the welfare of the people, but the growth is not the end of the human development. The purpose this study was to determine the role of direct purchasing in moderating the influence of the balancing funds to public welfare at the regency / city in the province of Bali. This study uses secondary data sourced from Statistics Center Corporation which were analyzed using multiple regression analysis with moderating variable. The analysis result showed that the Balanced Fund positively and was significant on public welfare, direct purchasing influenced positively and was significant on Public Welfare, while direct purchasing was not a moderating variable that could determine how much a direct role in moderating the influance of balancing funds to the public welfare.
Keywords: Balancing Funds; Direct Purchasing; The Public Welfare